2022
DOI: 10.3389/fneur.2021.767649
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Ruptured Very Small Intracranial Aneurysms: Complications, Recurrence Rate, and Clinical Outcomes

Abstract: Objective: The aim of this study was to evaluate the safety and efficacy of endovascular treatment for ruptured very small (≤3 mm) intracranial aneurysms (VSIAs).Methods: The clinical data and imaging results for 152 patients with VSIAs treated with coil embolization from August 2014 to June 2020 were retrospectively reviewed. The influential factors related to the preoperative complications, aneurysm recurrence, and clinical outcomes for these patients were analyzed.Results: Among 152 patients with ruptured V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…The wide-necked nature of VSIAs is a potent risk factor for coil protrusion into the parent artery. As in previous studies, [9,18,19] most (78%) of the VSIAs in our series were relatively wide-necked. To overcome this anatomical difficulty, we performed adjuvant techniques using stent-assisted coiling (SAC), catheter protection, and the double catheter technique, which were successful in preventing coil protrusion.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The wide-necked nature of VSIAs is a potent risk factor for coil protrusion into the parent artery. As in previous studies, [9,18,19] most (78%) of the VSIAs in our series were relatively wide-necked. To overcome this anatomical difficulty, we performed adjuvant techniques using stent-assisted coiling (SAC), catheter protection, and the double catheter technique, which were successful in preventing coil protrusion.…”
Section: Discussionsupporting
confidence: 86%
“…In recent single-center studies, IPR rates were reportedly lowered to 1.4% [10] and 1.3%. [9] In our study, IPR occurred in 3 patients (an IPR rate of 2.6%), which is an acceptable result consistent with previous studies. As previously reported, the favorable result of the low IPR rate in our study may be attributed to the use of advanced endovascular devices and cautious coiling procedures aimed at reducing the risk of IPR.…”
Section: Intraprocedural Rupturesupporting
confidence: 92%
See 1 more Smart Citation
“…With continuous progress in endovascular treatment technology and concept, as well as rapid development in new materials and equipment, endovascular treatment technology has been widely used in the treatment of intracranial aneurysms. Compared with surgical clipping, interventional embolization of aneurysms has the advantages of less trauma, faster recovery, and lower surgical risk, and has been accepted by the majority of patients as one of the first choices for the treatment of intracranial aneurysms ( 25 , 27 31 ). However, the recurrence rate was significantly higher than that of surgical clipping ( 2 , 19 – 21 ), with the recurrent ruptured hemorrhage of embolized aneurysms characterized by high mortality and disability, requiring repeated endovascular embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Although guidelines for the treatment of tiny intracranial aneurysms are lacking, commonly applied strategies include surgical clipping and endovascular embolization. Clipping is not ideal for treating tiny aneurysms because it usually causes parent artery narrowing and is associated with a high incidence of complications ( 15 ). In a series of 32 tiny aneurysms (≤ 3 mm) that were surgically clipped, Rahmanian et al reported a 30.8% intraoperative aneurysm rupture rate and 11.5% mortality ( 16 ).…”
Section: Discussionmentioning
confidence: 99%